PRESCRIPTION PATTERN OF CARDIOVASCULAR AND/OR ANTIDIABETIC DRUGS IN ABUJA DISTRICT HOSPITALS - OSUAFOR, NKEIRUKA GRACE; UKWE, CHINWE VICTORIA; OKONTA, MATTEW JEGBEFUME (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The study aimed to describe the prescription pattern of cardiovascular and/or anti-diabetic drugs and adherence to the World Health Organization (WHO) prescribing indicators in Abuja District Hospitals. Methods: This descriptive retrospective study was carried out in Asokoro and Maitama District Hospitals Abuja. One thousand and nine prescriptions that contained a cardiovascular drug (CVD) and/or anti-diabetic drug issued between June 2017 and May 2018 from the Medical Outpatient Department were analyzed. Data were collected from the pharmacy electronic database, prescription pattern and adherence to WHO prescribing indicators were assessed. The analysis was done using descriptive statistics. Results were presented as percentages, means, and standard deviations. Results: The frequency of treatment was higher among women (58.8%) and the age group of 41–60 (54.8%). The average number of drugs prescribed was 3.3±1.6: the percentage of drugs prescribed in generic was (64%) and (78.8%) were from the Essential Drug List (EDL). Calcium Channel Blockers (CCB, 71.7%) and Biguanides (B, 92.4%) were the most prescribed CVD and anti-diabetic drug. The majority of the CVD (74.5%) and diabetes (63.6%) patients were on combination therapy. The most frequent CVD combination was CCB plus Angiotensin-Converting Enzyme Inhibitors/Angiotensin Receptor Blockers (29.7%). Compared to men, the proportion of females taking one or more CVD (61.3%) or antidiabetic (56.4%) was higher. Conclusion: The prescribing indicators are not optimal in Abuja district hospitals. Women received more treatment for cardiovascular and diabetes diseases than men while the age range of 41-60 was more treated than other age groups.